HEC-RAS SIMULATION OF FLOOD MANAGEMENT IN SERUYAN RIVER: A Case Study of Mekar Indah Village, East Seruyan Hilir and UPT Tanggul Harapan Pematang Limau Village, Seruyan Hilir - Zulianto, Iwan; Yusuf, Noor Syarifuddin; Redin, Herry; Amelia, Vera; Nomeritae, Nomeritae; Misrita, Misrita (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
In 2020 and 2021, there was a big flood in (Technical Implementation Unit) UPT Tanggul Harapan, Pematang Limau Village, Seruyan Hilir District and Mekar Indah Village, Seruyan Hilir Timur District and it forced some people to flee their homes. The overflowing of Seruyan River is caused by high intensity of rain and river flooding from the headwaters of Seruyan. This condition occurred because of Mekar Indah Village and UPT. Tanggul Harapan is in a downstream location. The main objective of this research is to find out the effective way of controlling floods in the Seruyan River. The calculation result of flood peak volume is obtained by using the synthesis of hydrograph units using the SCS and Snyder methods. The results of this research indicated that the design of periodic re-rain for 50 years prior to the handling of floods in the area of UPT Tanggul Harapan occurred flooding of 94.96% of the entire area of UPT Tanggul Harapan. Meanwhile, in Mekar Indah Village occurred 40.72%, after simulating flood handling in making an embankment along 20111 m, elevation 5 m above sea level, top width of the embankment 5 m and 4 units of floodgates. It indicated a significant change in the flood area in UPT Tanggul Harapan to only 1.23%, while in Mekar Indah Village it is 0.80%. The simulation result indicated that flood management by making embankment is able to reduce the flood area by 93.19% in UPT Tanggul Harapan and 39.92% in Mekar Indah Village.